2017
DOI: 10.1161/strokeaha.117.017327
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ischemic Stroke After Moderate to Severe Traumatic Brain Injury

Abstract: Background and Purpose Traumatic brain injury (TBI) leads to nearly 300 000 annual US hospitalizations and increased lifetime risk of acute ischemic stroke (AIS). Occurrence of AIS immediately after TBI has not been well characterized. We evaluated AIS acutely after TBI and its impact on outcome. Methods A prospective database of moderate to severe TBI survivors, admitted to inpatient rehabilitation at 22 Traumatic Brain Injury Model Systems centers and their referring acute-care hospitals, was analyzed. Out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 33 publications
3
60
1
3
Order By: Relevance
“…There is also a positive correlation between the degree of injury and the severity of complications. Therefore, it is important to research and implement efficient interventions for TBI in order to reduce the abovementioned complications (Scott et al, 2009;Hayes et al, 2017;Kowalski et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There is also a positive correlation between the degree of injury and the severity of complications. Therefore, it is important to research and implement efficient interventions for TBI in order to reduce the abovementioned complications (Scott et al, 2009;Hayes et al, 2017;Kowalski et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With regards to TBI, there are no studies that have assessed if complement plays a role in the hemostatic disturbance that is seen following injury. Based on the data provided in this review, one might instinctively suggest that any such interaction would result in increased thrombosis, and could thus explain the prothrombotic sate that is seen days to weeks following TBI [53][54][55][56][57]. However, it should be noted that the initial bleeding tendency that is seen following TBI is also believed to be due to unregulated thrombosis, culminating in a consumptive coagulopathy that leads to the exacerbation of hemorrhagic lesions [2].…”
Section: Discussionmentioning
confidence: 96%
“…Currently, there is controversy within the literature regarding the exact nature of hemostatic perturbations after TBI, and evidence exists for the presence of both a hypercoagulable and hypocoagulable state [2]. For example, while the initial head injury often leads to increased bleeding tendency and the exacerbation of hemorrhagic lesions [2,[46][47][48], TBI is also independently associated with an increased risk for venous thromboembolism [49][50][51][52] and ischemic stroke [53][54][55][56][57]. Autopsy studies have also revealed that micro-thrombosis is present in the majority patients who have died from head trauma [58].…”
Section: Hemostatic Disturbance In Tbimentioning
confidence: 99%
“…20 The mechanoporation of the plasmatic membrane leads to an increase in the cell membrane permeability and its subsequent ionic imbalance, which promotes the release of neurotransmitters (due to the entrance of Ca 2+ ) to the synaptic cleft, mainly of glutamate. 20 In parallel, the mechanoporation produced by physical damage and exposure to traumatic events can generate an ischemic brain environment, 21 where the supply of oxygen and glucose to the brain is reduced; 22 a situation that can give way to events influencing cell damage.…”
Section: Neuronal Damaged Induced By Tbimentioning
confidence: 99%